Evaluasi Model CIPP pada Program Pendidikan Berbasis Keunggulan Lokal Batik: Studi di SMA Negeri 1 Sokaraja - Pasa Iftinan Abiyyah; Fajar (Media Manajemen Pendidikan, 2026)
This study aims to evaluate the Lokal Batik Excellence-Based Education Program at SMA Negeri 1 Sokaraja using the CIPP model. This research used a descriptive qualitative approach with data collection conducted through observation, interviews, documentation, and literature study. The subjects of this study were the vice principal for curriculum, PKWU teachers, PBKL staff, and students. The results of the Context evaluation showed a shift in objectives from cultural preservation to a focus on education and entrepreneurship based on contextual dynamics that were also undergoing change. In the Input component, there were changes in staff arrangements and operational budgets, which were originally funded by the local government but now come entirely from Bos funds. The Process evaluation shows that PBKL Bati reached its peak of success in the second period through batik cloth production and public education services. The Product component saw a significant increase in program results and achievements, but experienced a decline at the end of the third period. Based on the CIPP evaluation, it was concluded that changes in activities, operational scale, and results in each period were influenced by the development of objectives, policy changes, staff arrangements, and funding.